THU0264 Responsiveness of lupuspro v1.8 among chinese patients with lupus. (15th June 2017) - Mok, CC; Block, J; Jolly, M
Abstract : Background: LupusPRO v1.7 is a patient reported outcome tool for patients with systemic lupus erythematosus (SLE) that has undergone psychometric validation and responsiveness studies in the US. Objectives: To report results on responsiveness of LupusPRO among Chinese patients with SLE. Methods: 430 patients with SLE meeting the ACR classification criteria were recruited in Hong Kong, China at a single center for this observational study. LupusPRO scores from two visits one year apart were analyzed for responsiveness and Minimal Clinically Important Difference (MCID) against patient report and physician assessed anchors of changes in health. Two patient reported anchors were used (Global change in health and item 2 of Short Form 36 form). Physician assessed anchors of change in health were disease activity (Physician global assessment-PGA, SELENA-SLEDAI) and damage (SLICC-SDI/ACR). Change in PGA of ≥0.3 and SELENA-SLEDAI of ≥4 in either direction was used to define worsening in disease activity. Our primary outcomes of interest were was summary HRQOL and HRQOL domains, as non HRQOL domains tend not to change over short time periods. Analysis of variance was used to compare changes in LupusPRO summary and domain scores against the anchors. Results: Mean (SD) age of participants was 42 (14) years. Ninety five percent were women. Mean (SD) PGA, SELENA-SLEDAI and SDI at baseline were 0.5 (0.5), 2.9 (3.0) and 0.7 (1.2) respectively. Summary HRQOL, and HRQOL domains (Lupus Symptoms, Physical Health, Pain-Vitality, Emotional Health and Body Image) were responsive to changes in patient reported and physician assessed health status (disease activity and damage) (Table 1 ). Procreation and Cognition domains showed responsive trends with patient reported change in health status, while Lupus Medications domain was responsive additionally to changes in Damage. Conclusions: LupusPRO summary HRQOL and HRQOL domains show responsiveness to changes in patient-reported and physician assessed changes in health status in this observational study among Chinese SLE patients. Results support inclusion of LupusPRO into larger clinical trials to allow for robust estimates of responsiveness. Disclosure of Interest: None declared